Thickener and cast film
The use of a thickener with specific methacrylic resin and additives in methacrylic resin syrups addresses the issues of polymerization stalling and color deterioration, ensuring stable and high-quality cast polymerization and films.
Patent Information
- Application Number
- JP2024096172
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-06-13
- Publication Date
- 2025-04-08
AI Technical Summary
The existing methods for producing methacrylic resin syrups for cast polymerization face challenges such as stalling of polymerization and deterioration of color due to the absence of the Tromsdorf effect, leading to solidification issues during the polymerization reaction.
A thickener containing a specific amount of methacrylic resin with a weight average molecular weight of 300,000 to 5,000,000, along with docosan, 4-tert-butylcyclohexanol, or fatty alcohols with 12 or more carbon atoms, is used to control the heat of polymerization and prevent stalling.
The proposed solution effectively prevents the stalling of polymerization and deterioration of color by controlling the heat of polymerization, thereby preventing solidification during cast polymerization and maintaining the quality of the cast film.
Smart Images

Figure 2025056708000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thickener and a cast film. [Background technology]
[0002] Methacrylic resins have excellent properties such as transparency, weather resistance, and mechanical properties, and are therefore used in many fields, such as lighting materials, optical materials, signs, displays, decorative materials, and building materials. Cast polymerization, in which methyl methacrylate monomer and various additives are added to a mold and polymerized, has long been used, particularly for applications requiring toughness such as aquariums, and for applications in artificial marble for use in bathtubs, vanities, kitchen sinks, etc. In cast polymerization, in order to improve handling and prevent inorganic filler settling, a syrup with increased viscosity is made by dissolving methacrylic resin as a thickener, or a syrup with increased viscosity is made by prepolymerizing part of the monomer. Methacrylic resins are also used in the production of methacrylic resin films. When producing methacrylic resin films, there is a production method called a solution casting method in which a methacrylic resin or the like is dissolved in a solvent and formed into a film while degassing the solvent, and the film obtained by this method is also called a cast film.
[0003] As an example of a thickener containing a methacrylic resin, Patent Document 1 discloses a thickener for cyanoacrylate adhesives that contains an alkyl acrylate monomer unit having an alkyl group with 4 or more carbon atoms as a copolymerization component of the methacrylic resin.
[0004] Patent Document 2 discloses a thickener containing a methacrylic resin that has excellent stability when exposed to 50° C. / 95% Rh in methyl methacrylate.
[0005] Patent Document 3 discloses that when a methacrylic resin plate is produced by cast polymerization, a colorless and transparent methacrylic resin plate can be obtained by polymerization using a specific mercapto group-containing compound. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2022 / 070868 [Patent Document 2] JP 2018-178076 A [Patent Document 3] Japanese Patent Application Publication No. 8-109212 Summary of the Invention [Problem to be solved by the invention]
[0007] However, depending on the type of methacrylic resin used as a thickener, when producing a syrup for cast polymerization, polymerization of the monomer may progress while dissolving the methacrylic resin thickener in the methyl methacrylate monomer, causing solidification.
[0008] Usually, when suspension polymerization or bulk polymerization is carried out using methyl methacrylate monomer, the diffusion rate of growing radicals at the polymer end decreases due to an increase in viscosity in the later stage of polymerization, which makes it more difficult for termination reactions to occur due to collisions between radicals than in the early stage of polymerization, and as a result, the growing reaction proceeds more easily and the polymerization rate increases. This is known as the Trommsdorff effect. When producing a syrup, it is preferable to use a methacrylic resin with as high a molecular weight as possible as a thickener in order to obtain the desired viscosity at a low concentration. However, when polymerizing monomers to produce a methacrylic resin with a high molecular weight, there is a problem in that heat generation due to the Trommsdorff effect becomes large and it becomes difficult to control the heat removal. On the other hand, if the polymerization conditions are made milder in order to prevent this, the polymerization time will be extended, resulting in poor productivity. In addition, there is a problem that the Trommsdorff effect will not occur, i.e., the polymerization will not be accelerated, and the phenomenon of an increase in residual monomers will frequently occur. Furthermore, in polymerization systems in which the Trommsdorff effect does not occur, the reaction stops when there is a large amount of residual monomer, and so during the process of maturing at 90°C or higher to reduce the remaining monomer, the reaction proceeds violently and the beads coalesce, taking with them the suspending agent, resulting in a problem of poor color when used in cast polymerization or cast film.
[0009] Therefore, an object of the present invention is to provide a thickener that can prevent polymerization stall and deterioration of color due to the failure to manifest the Trommsdorff effect during polymerization, and that can prevent solidification due to the progression of the polymerization reaction of methyl methacrylate monomer during dissolution when used in cast polymerization. Another object of the present invention is to provide a cast film in which deterioration of color tone is prevented. [Means for solving the problem]
[0010] In order to solve the above problems, the present inventors have conducted intensive research and have surprisingly found that a thickener containing a specific amount of a methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000 and a specific amount of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms contributes to controlling the heat generated by polymerization during the production of methacrylic resin and preventing the stall of polymerization due to the failure to manifest the Trommsdorff effect during polymerization. In addition, it has been found that the use of such a thickener in cast polymerization can prevent the polymerization reaction of methyl methacrylate from progressing and solidifying during dissolution.
[0011] That is, the present invention is as follows.
[0012] [1] 90% by mass or more of methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000, and A thickening agent containing 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms.
[0013] [2] The thickener according to [1], wherein the methacrylic resin contains 95% by mass or more of methyl methacrylate monomer units and optionally contains 0 to 5% by mass of acrylic ester monomer units.
[0014] [3] The thickener according to [1] or [2], wherein the methacrylic resin contains 95 to 99.9 mass% of methyl methacrylate monomer units and 0.1 to 5 mass% of acrylic ester monomer units.
[0015] [4] The thickener according to [2] or [3], wherein the acrylic acid ester monomer unit has an alkyl group having 4 or more carbon atoms.
[0016] [5] The intrinsic viscosity of the methacrylic resin is 100 to 1000 cm 3 / g of the thickener according to any one of [1] to [4].
[0017] [6] The thickener according to any one of [1] to [5], characterized in that the methacrylic resin is polymerized using an initiator having a 10-hour half-life temperature of less than 65°C.
[0018] [7] The thickener according to any one of [1] to [6], wherein the methacrylic resin has an active oxygen content of 0.001 to 0.01% by mass upon polymerization.
[0019] [8] The thickener according to any one of [1] to [7], which is for use in cast polymerization.
[0020] [9] The thickener according to any one of [1] to [8], which is for use in cast polymerization of a methacrylic resin sheet.
[0021]
[10] The thickener according to any one of [1] to [9], which is used for cast polymerization of artificial marble.
[0022]
[11] The thickener according to any one of [1] to
[10] , which has a volume average particle size of 50 μm to 500 μm when used in the form of beads.
[0023]
[12] The method for producing a thickener according to any one of [1] to [5] and [7] to
[11] , wherein the methacrylic resin is polymerized using a polymerization initiator having a 10-hour half-life temperature of less than 65°C.
[0024]
[13] 90% by mass or more of methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000, and A cast film containing 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms. Effect of the Invention
[0025] According to the present invention, it is possible to provide a thickener that can prevent polymerization stall and deterioration of color due to the failure to manifest the Trommsdorff effect during polymerization, and can prevent solidification due to the progression of the polymerization reaction of methyl methacrylate during dissolution when used in cast polymerization. Furthermore, according to the present invention, a cast film in which deterioration of color tone is prevented can be provided. [Brief description of the drawings]
[0026] [Figure 1] 1 is a graph showing the temperature trend in the polymerization reaction of Example 1. [Diagram 2] 2 is a graph showing a temperature trend in the polymerization reaction of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described in detail. The present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention.
[0028] [Thickener] The thickener of the present embodiment contains 90% by mass or more of a methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000, and The composition is characterized by containing 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms. The thickener of the present embodiment can prevent polymerization stalling and deterioration of color due to the failure to exhibit the Trommsdorff effect during polymerization, and can prevent solidification due to the progression of the polymerization reaction of methyl methacrylate during dissolution when used in cast polymerization.
[0029] The thickener of the present embodiment contains at least a methacrylic resin. The thickener may contain only a methacrylic resin as a resin component, or may contain a methacrylic resin and another resin. The thickener preferably contains only a methacrylic resin as a resin component. The thickener may contain one type of methacrylic resin alone or two or more types of methacrylic resin in combination. In one example, the thickener preferably contains only a single methacrylic resin as a resin component. The content of the methacrylic resin in the thickener is 90% by mass or more, more preferably 95% by mass or more, and further preferably 97% by mass or more.
[0030] The thickener of the present embodiment is preferably for cast polymerization. Cast polymerization is a method in which an additive such as a polymerization initiator is added to the monomer methyl methacrylate, and the monomer is poured into a mold to polymerize and obtain a molded body. In cast polymerization, in order to improve the handling property when pouring the monomer methyl methacrylate or the like into a mold, there is a method in which a part of the polymerization monomer is polymerized to obtain a syrup, and a method in which a thickener is dissolved in a monomer to obtain a syrup as in the present invention. In addition, the thickener of the present embodiment is more preferably for cast polymerization of methacrylic resin sheets and cast polymerization of artificial marble. The thickener of the present embodiment is also preferably used for a cast film, in which the thickener is dissolved in a solvent, cast into a sheet, and then the solvent is evaporated to obtain a film.
[0031] (Methacrylic resin) The methacrylic resin contained in the thickener of the present embodiment has a weight average molecular weight (Mw) of 300,000 to 5,000,000 as measured by gel permeation chromatography (GPC). If Mw is less than 300,000, the amount of methacrylic resin used to make the syrup (a solution in which the methacrylic resin is dissolved) have a predetermined viscosity increases, which is not preferable because the mechanical properties of the resulting adhesive may be inferior. On the other hand, Mw is preferably 5,000,000 or less from the viewpoint of solubility and property stability when used as a thickener. Since the desired viscosity can be obtained by adding a small amount, Mw is more preferably 300,000 to 4,500,000, even more preferably 350,000 to 1,500,000, and particularly preferably 400,000 to 1,300,000. Furthermore, in order to obtain a desired viscosity by adding a small amount, it is also preferable that the Mw is 1,000,000 to 5,000,000.
[0032] The molecular weight distribution Mw / Mn, which is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the methacrylic resin measured by gel permeation chromatography (GPC), is preferably 1.7 or more and 2.5 or less. From the viewpoint of ease of production, the molecular weight distribution Mw / Mn is more preferably 1.8 or more. Moreover, from the viewpoint of suppressing residuals during dissolution and improving solubility, it is more preferably less than 2.5, even more preferably 2.4 or less, particularly preferably 2.3 or less, and particularly preferably less than 2.3.
[0033] The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). A calibration curve is prepared in advance from the elution time and the weight average molecular weight using a standard methacrylic resin that is available as a reagent with a known monodisperse weight average molecular weight and an analytical gel column that is eluted from the high molecular weight component. The molecular weight of each sample can be measured from the calibration curve. Specifically, the molecular weight may be measured by the method described in the Examples below. When the molecular weight is higher than that of a standard methacrylic resin, the absolute molecular weight may be measured by GPC-MALS. Specifically, the absolute molecular weight may be measured by the method described in the Examples below.
[0034] (Docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols with 12 or more carbon atoms) The thickener of the present embodiment contains 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms. By polymerizing monomers such as molded products so that these substances are present, it is possible to control the heat generated by polymerization and also to contribute to preventing stalling of polymerization due to failure to manifest the Trommsdorff effect during monomer polymerization. The content of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms is preferably 50 to 1000 ppm by mass, more preferably 70 to 350 ppm by mass. When the thickener contains two or more of the above compounds such as docosane, the content is the total content of those compounds.
[0035] The aliphatic alcohol having 12 or more carbon atoms is preferably an aliphatic alcohol having 12 to 18 carbon atoms, and more preferably an aliphatic alcohol having 12 to 16 carbon atoms.
[0036] Examples of the aliphatic alcohol having 12 or more carbon atoms include 1-hexadecanol and 1-tetradecanol. Examples of compounds that generate aliphatic alcohols having 12 or more carbon atoms include bis(hexadecyloxycarbonyl) peroxide and 1,1'-[dioxybis(carbonyloxy)]ditetradecane.
[0037] The above compounds (docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms) are generated, for example, as decomposition products of polymerization initiators used in the production of methacrylic resins. For example, when dilauroyl peroxide is used as a polymerization initiator, docosane is generated as a decomposition product. When di-(4-tert-butylcyclohexyl)peroxydicarbonate is used as a polymerization initiator, 4-tert-butylcyclohexanol is generated. When bis(hexadecyloxycarbonyl) peroxide is used as a polymerization initiator, 1-hexadecanol is generated. When 1,1'-[dioxybis(carbonyloxy)]ditetradecane is used as a polymerization initiator, 1-tetradecanol is generated.
[0038] <Copolymerization component> The methacrylic resin preferably contains 95% by mass or more of methyl methacrylate monomer units and optionally contains 0 to 5% by mass of acrylic ester monomer units. The methacrylic resin preferably contains 95 to 99.9% by mass of methyl methacrylate monomer units and 0.1 to 5% by mass of acrylic ester monomer units. The methacrylic resin more preferably contains 96 to 99.8% by mass of methyl methacrylate monomer units and 0.2 to 4% by mass of acrylic ester monomer units, and further preferably contains 97 to 99.7% by mass of methyl methacrylate monomer units and 0.3 to 3% by mass of acrylic ester monomer units. The methacrylic resin may or may not contain other monomer units than the methyl methacrylate monomer units and the acrylic ester monomer units.
[0039] The acrylic acid ester monomer unit preferably has an alkyl group having 4 or more carbon atoms. The number of carbon atoms in the alkyl group of the acrylic acid ester monomer unit is preferably 4 to 8. As the acrylic acid ester monomer unit having an alkyl group having 4 or more carbon atoms, an acrylic acid ester monomer unit having an alkyl group having 4 to 8 carbon atoms, such as n-butyl acrylate, sec-butyl acrylate, or 2-ethylhexyl acrylate, is preferred. From the viewpoints of availability and odor reduction, n-butyl acrylate monomer unit is particularly preferred.
[0040] The methacrylic resin may be composed only of methyl methacrylate monomer units and acrylic ester monomer units having an alkyl group having 4 or more carbon atoms, or may further contain other monomer units such as other vinyl monomer units copolymerizable with methyl methacrylate.
[0041] The other monomer units may be vinyl monomers copolymerizable with methyl methacrylate, specifically, alkyl methacrylates having an alkyl group with 2 to 18 carbon atoms; alkyl acrylates having an alkyl group with 1 to 3 carbon atoms; α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and their alkyl esters such as maleic acid, fumaric acid, itaconic acid, etc.; aromatic vinyl compounds such as styrene, α-methylstyrene, and styrene having a substituent on the benzene ring; cyanide vinyl compounds such as acrylonitrile and methacrylonitrile; maleic anhydride, maleimide, N-substituted maleimide; ethylene glycol di(meth)acrylate, diethylene glycol Examples of the ester include ethylene glycol or its oligomers, such as di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate, in which both terminal hydroxyl groups are esterified with acrylic acid or methacrylic acid; neopentyl glycol di(meth)acrylate, di(meth)acrylate, and other hydroxyl groups of two alcohols are esterified with acrylic acid or methacrylic acid; trimethylolpropane, pentaerythritol, and other polyhydric alcohol derivatives are esterified with acrylic acid or methacrylic acid; and polyfunctional monomers such as divinylbenzene. These can be used alone or in combination of two or more. From the viewpoint of odor suppression, when an alkyl acrylate having an alkyl group with 1 to 3 carbon atoms is contained, the mass ratio of the alkyl acrylate monomer unit having an alkyl group with 1 to 3 carbon atoms is preferably less than 0.1 mass% relative to 100 mass% of all monomer units constituting the methacrylic resin. It is more preferable that the methacrylic resin does not contain an alkyl acrylate having an alkyl group with 1 to 3 carbon atoms.
[0042] In this embodiment, other monomer units may be copolymerized within a range that does not impair the effects of the present invention. Considering solubility, odor during dissolution, etc., when the total amount of methyl methacrylate monomer units and acrylic acid ester monomer units having an alkyl group with 4 or more carbon atoms is 100 parts by mass, the mass ratio of other monomer units derived from other monomers copolymerizable with methyl methacrylate is preferably 0 to 20 parts by mass, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less.
[0043] In 100 parts by mass of the methacrylic resin, the total mass proportion of the methyl methacrylate monomer units and the acrylic ester monomer units having an alkyl group having 4 or more carbon atoms is preferably 80 parts by mass or more, more preferably 85 parts by mass or more, even more preferably 90 parts by mass or more, still more preferably 95 parts by mass or more, and particularly preferably 100 parts by mass.
[0044] -Intrinsic viscosity- The methacrylic resin used in the thickener of the present invention has an intrinsic viscosity of 100 cm 3 / g~1000cm 3 The intrinsic viscosity can be measured by the method described in the Examples below. 3 If the intrinsic viscosity is less than 1000 cm / g, the amount of methacrylic resin used to make the syrup (a solution containing dissolved methacrylic resin) have to be increased to a certain viscosity, which may result in inferior mechanical properties of the resulting adhesive, etc., and is therefore undesirable. On the other hand, from the viewpoint of solubility and property stability when used as a thickener, the intrinsic viscosity should be 1000 cm 3 The intrinsic viscosity is preferably 110 to 900 cm / g or less. 3 / g, and more preferably 120 to 800 cm 3 / g.
[0045] <Polymerization initiator> The methacrylic resin used in the thickener of the present invention is preferably polymerized using a polymerization initiator having a 10-hour half-life temperature of less than 65° C. When a polymerization initiator having a 10-hour half-life temperature of less than 65° C. is used, the polymerization initiator can be consumed almost entirely in the polymerization process of the methacrylic resin, and it is possible to prevent the polymerization of the monomer caused by the remaining polymerization initiator in the thickener from proceeding and solidifying while the methacrylic resin is being dissolved in the methyl methacrylate monomer that is the raw material for the molded body or the like. As the polymerization initiator satisfying the above requirements, dilauroyl peroxide, di-(4-tert-butylcyclohexyl) peroxydicarbonate, t-butyl peroxypivalate, t-hexyl peroxypivalate, and t-butyl peroxy-2-ethylhexanoate are preferred. The polymerization initiator is generally used in the range of 0.001 to 1% by mass relative to 100% by mass of the total mass of the methacrylic resin monomer used in the thickener, and additives used during polymerization such as the polymerization initiator and chain transfer agent.
[0046] When dilauroyl peroxide is used as a polymerization initiator, it is preferably used in the range of 0.01 to 0.5 mass%, more preferably in the range of 0.03 to 0.3 mass%, even more preferably in the range of 0.04 to 0.18 mass%, and most preferably in the range of 0.05 to 0.13 mass% (containing it in a monomer solution and polymerizing it), relative to 100 mass% of the total mass of the methacrylic resin monomers used in the thickener.
[0047] -Active oxygen content- The methacrylic resin used in the thickener of the present invention preferably has an active oxygen content of 0.001% by mass to 0.01% by mass during polymerization. The active oxygen content during polymerization can be calculated by (% by mass of polymerization initiator relative to 100% by mass of the total mass of monomers of the methacrylic resin used in the thickener) x (active oxygen content of polymerization initiator). When using a polymerization initiator with a large amount of active oxygen, it is preferable to set the amount of the polymerization initiator to a small amount. By setting the amount of the polymerization initiator in this way, it is possible to control the heat generated by polymerization in the polymerization using the thickener of the present invention, and also to contribute to preventing the stall of polymerization and the deterioration of color due to the failure to exhibit the Trommsdorff effect during polymerization.
[0048] The shape of the thickener of the present invention is not particularly limited, but is preferably in the form of pellets, flakes, beads, or powder. From the viewpoint of shortening the dissolution time and reducing unmelted matter, it is preferably in the form of beads or powder.
[0049] -Volume average particle size- The thickener of the present invention preferably has a volume average particle diameter of 50 to 500 μm when used in the form of beads. Since the dissolution time is shorter as the particle diameter is smaller, the volume average particle diameter of the thickener is preferably 500 μm or less, and from the viewpoint of suppressing scattering of beads during operation and reducing unmelted matter, it is preferably 50 μm or more. The volume average particle diameter is more preferably 70 to 400 μm, and most preferably 100 to 350 μm. The volume average particle size can be determined using the laser scattering method of Beckman Coulter LS13320.
[0050] -D90- The thickener of the present invention preferably has a particle size distribution D90 of less than 500 μm. The dissolution time is likely to be extended if large particles remain, not just the average particle size. The particle size distribution D90 is preferably less than 450 μm, more preferably less than 400 μm.
[0051] <Application> The thickener of the present invention is preferably used for methacrylic resin sheets, artificial marble, and cast films produced by cast polymerization.
[0052] <Methacrylic resin manufacturing method> The methacrylic resin can be produced, for example, using a monomer constituting the methacrylic resin, a polymerization initiator, a chain transfer agent, a suspending agent, other additives, and the like.
[0053] In producing the methacrylic resin, it is preferable to polymerize the methacrylic resin using a polymerization initiator having a 10-hour half-life temperature of less than 65°C.
[0054] In the method for producing a methacrylic resin, when the resin is produced by a radical polymerization method, a commonly used chain transfer agent can be used to adjust the molecular weight.
[0055] As the chain transfer agent, for example, mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tristhioglycolate, and pentaerythritol tetrakis(thioglycolate) are preferably used.
[0056] The chain transfer agent may be used in the range of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers constituting the methacrylic resin. The amount of the chain transfer agent is determined depending on the desired molecular weight.
[0057] As a polymerization method for the methacrylic resin, it is preferable to use suspension polymerization or emulsion polymerization. Since suspension polymerization gives particulate resin beads and emulsion polymerization gives powdery resin beads, it is advantageous in terms of operation when dissolving an appropriate amount as a thickener to adjust the syrup to the desired viscosity.
[0058] As for the polymerization method, suspension polymerization is preferable since the polymerization time is shorter in suspension polymerization than in emulsion polymerization.
[0059] As a method for polymerizing the methacrylic resin, it is preferable to use a method in which a suspending agent having an average particle size of 10 to 40 μm is dispersed in water and polymerized. Among them, it is preferable to disperse a suspending agent having an average particle size of 10 to 40 μm in water and perform one-stage suspension polymerization.
[0060] In the method for producing methacrylic resin, it is preferable to carry out polymerization with the average particle size of the suspending agent dispersed in the suspension polymerization water set to 10 to 40 μm. This makes it possible to control the standard deviation of the volumetric particle size of the methacrylic resin (e.g., methacrylic resin beads), stabilize the polymerization behavior, reduce the amount of heat removal, and improve productivity.
[0061] The average particle size of the suspension can be adjusted by appropriately selecting the particle size of the suspension used. Furthermore, a suspension with an appropriate average particle size can be obtained by mixing powders with different particle sizes.
[0062] In the method for producing a methacrylic resin, it is preferable to adjust the pH of the aqueous phase to a range of 4 to 7. By adjusting the pH of the aqueous phase to fall within this range, the standard deviation of the particle size of the beads can be controlled, and the polymerization behavior can be stabilized.
[0063] In the method for producing methacrylic resin, it is preferable to adjust the temperature of the suspending agent to 50°C to 90°C in advance and then add it to the water (50°C to 90°C) in the reactor. This makes it possible to adjust the average particle size of the methacrylic resin (e.g., methacrylic resin beads) and its variation.
[0064] Depending on the manufacturing method of the methacrylic resin, it is preferable to use an inorganic suspending agent rather than an organic suspending agent. In the case of an organic suspending agent, the variation in the average particle size of the beads tends to be too small. Here, examples of the organic suspending agent include polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, gelatin, polyvinyl acetate, etc.
[0065] The inorganic suspending agent preferably contains an inorganic compound containing calcium and / or aluminum, and examples of the inorganic suspending agent include calcium phosphate such as tricalcium phosphate (calcium phosphate tertiary), calcium carbonate, aluminum hydroxide, etc. In particular, the inorganic suspending agent more preferably contains an inorganic compound containing aluminum.
[0066] The suspending agent may further contain a suspending aid such as polyethylene glycol, sodium ethylenediaminetetraacetate, sodium lauryl sulfate, etc. The suspending aid may be contained in an amount of 0.01 to 10% by mass relative to 100% by mass of the suspending agent.
[0067] The suspending agent is preferably used by mixing it with the monomer raw material in water.
[0068] <Cleaning method> In the method for producing a methacrylic resin, it is preferable to carry out operations such as acid washing, water washing, and alkali washing in order to remove the suspending agent. The number of times that these washing operations are carried out may be selected optimally from the viewpoints of work efficiency and suspending agent removal efficiency, and may be repeated once or multiple times.
[0069] The temperature for washing may be selected optimally taking into consideration the efficiency of removing the suspending agent and the degree of coloration of the resulting polymer, and is preferably 20 to 100° C. The temperature for washing is more preferably 30 to 95° C., further preferably 40 to 95° C., and particularly preferably 50 to 80° C.
[0070] The washing time per washing is preferably 10 to 180 minutes, more preferably 20 to 150 minutes, from the viewpoints of washing efficiency and reduction in odor when used as a thickening agent.
[0071] The pH of the washing solution used in washing may be within a range that allows removal of the suspending agent, and is preferably pH 1 to 12. When performing acid washing, the pH is preferably pH 1 to 5, more preferably pH 1.2 to 4, from the viewpoint of the efficiency of removing the suspending agent and the color tone of the resulting polymer. The acid used in acid washing may be any acid that allows removal of the suspending agent, and is not particularly specified, but a conventionally known inorganic acid or organic acid may be used. Examples of suitable acids include inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and boric acid, and each may be used in a diluted solution diluted with water or the like. Examples of organic acids include those having a carboxyl group, a sulfo group, a hydroxyl group, a thiol group, and an enol group. In consideration of the effect of removing the suspending agent and the color tone of the resulting resin, nitric acid, sulfuric acid, and an organic acid having a carboxyl group are more preferable.
[0072] After the acid washing, it is preferable to further perform washing with water or washing with an alkali, more preferably washing with hot water of 50°C or higher, and even more preferably washing with hot water of 50°C or higher, followed by further washing with an alkali and / or washing with hot water of 50°C or higher.
[0073] By adjusting the pH of the slurry after washing to 2 or more and 9 or less, preferably 4 or more and 7 or less, more preferably 5 or more and 6.8 or less, and particularly preferably 5.5 or more and 6.5 or less, a thickener having excellent storage stability and light resistance can be obtained.
[0074] (Additives) The thickener of the present embodiment may optionally contain other additives. The additives are not particularly limited as long as they can exert the effects of the present invention, and may be appropriately selected depending on the purpose.
[0075] Examples of additives include, but are not limited to, ultraviolet absorbers, heat stabilizers, light stabilizers; plasticizers; flame retardants; flame retardant assistants; curing agents; curing accelerators; antistatic agents; conductivity imparting agents; stress relaxation agents; mold release agents; crystallization accelerators; hydrolysis inhibitors; lubricants; impact imparting agents; sliding property improvers; compatibilizers; nucleating agents; reinforcing agents; flow adjusters; dyes; sensitizers; colorants; anti-settling agents; anti-sagging agents; fillers; defoamers; light diffusing fine particles; rust inhibitors; antibacterial agents; anti-fungal agents; anti-fouling agents; conductive polymers, and the like. The content of the additive in the thickener is not particularly limited, but may be, for example, 0.1% by mass or less.
[0076] The thickener of the present embodiment may be the methacrylic resin obtained by the above-mentioned method as it is, or may be mixed with other methacrylic resin compositions to form a thickener.
[0077] [Cast film] The cast film of the present embodiment contains 90% by mass or more of a methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000, and The composition is characterized by containing 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms. The cast film of this embodiment is prevented from deteriorating in color. The components contained in the cast film (for example, methacrylic resin) are similar to those of the thickener, and detailed description thereof will be omitted.
[0078] In another embodiment, the cast film is a cast film that includes the thickener of the present embodiments.
[0079] The cast film of this embodiment can be produced by a solution casting method in which the thickener of this embodiment is dissolved in a solvent, cast onto the surface of a smooth drum or stainless steel belt, and heated and dried to evaporate the solvent to produce a film.
[0080] The cast film of the present embodiment can be used, without being limited thereto, for packaging applications of fibers, foods, and daily necessities, and optical films such as protective films for polarizing plates, and the like. EXAMPLES
[0081] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples in any way.
[0082] <Raw materials> The raw materials used were as follows: Methyl methacrylate (MMA): Asahi Kasei (containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA): Mitsubishi Chemical (contains 15 ppm by mass of 4-methoxyphenol as a polymerization inhibitor) Butyl acrylate (BA): Toa Gosei (contains 15 ppm by mass of 4-methoxyphenol as a polymerization inhibitor) 2-Ethylhexyl thioglycolate (EHTG): Arkema Dilauryl peroxide (LPO): Made by Nippon Oil & Fats, active oxygen content 4.01% Di-(4-tert-butylcyclohexyl) peroxydicarbonate: manufactured by Nouryon Chemical Co., Ltd., product name "Perkadox 16", active oxygen content 4.01% Bis(hexadecyloxycarbonyl) peroxide: manufactured by Nouryon Chemical Co., Ltd., product name "Trigonox 24-FL", active oxygen content 2.80% 1,1'-[dioxybis(carbonyloxy)]ditetradecane: manufactured by Nouryon Chemical Co., Ltd., trade name "Perkadox 26", active oxygen content 3.11% tert-Butyl 2-ethylperoxyhexanoate: NOF Corp., trade name "Perbutyl O", active oxygen content 7.1% Sodium lauryl sulfate: Fujifilm Wako Pure Chemical Industries, used as a suspension aid Tetrasodium ethylenediaminetetraacetate dihydrate (EDTA): Kishida Chemical Aluminum hydroxide: Nippon Light Metal's SBX73, B303, B153, and B103 were used, and the average particle size was adjusted by appropriately mixing each. Docosan: manufactured by Tokyo Chemical Industry Co., Ltd.
[0083] [I. Production of methacrylic resin beads for use as thickener] Example 1 -Adjustment of suspension agent- 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 33 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added to a vessel equipped with a stirrer equipped with four inclined paddle blades and mixed to obtain a mixed liquid (a1). The average particle size of the suspending agent in the mixed liquid (a1) was 33 μm, and the pH of the obtained mixed liquid (a1) was 5.5. The obtained mixed liquid (a1) was heated to 70°C.
[0084] -Polymerization reaction- Next, 25 kg of water was added to a 60L reactor and the temperature was raised to 80°C, and a monomer solution obtained by mixing 3 kg of the mixed liquid (a1), 21 kg of the monomer raw material having the composition shown in Table 1, 17 g of EHTG, and 10 g of LPO was added to the reactor. Then, the temperature was kept at about 80°C to carry out suspension polymerization, and a peak of heat generation was observed 180 minutes after the monomer solution was added. The peak temperature was 83°C. Then, the temperature was raised to 93°C at a rate of 1°C / min, and the temperature was kept at about 93°C for 45 minutes, and the polymerization reaction was essentially terminated to obtain a polymer slurry. Next, the obtained polymer slurry was cooled to 50°C. 20% by mass of sulfuric acid was added to the polymer slurry to dissolve the suspending agent, and a polymerization reaction solution was obtained. Next, the obtained polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, filtered, and separated into bead-like methacrylic resin particles and suspension waste liquid. The pH of the suspended waste liquid was 3.3. The temperature trend during the polymerization reaction is shown in Figure 1.
[0085] -Cleaning process- Then, an approximately equal amount of ion-exchanged water at about 70°C was added to the bead-shaped methacrylic resin particles, and the mixture was stirred, washed, and filtered. Similarly, washing with ion-exchanged water at about 70°C was performed once more (a total of two water washes) to obtain a slurry polymer solution. A sodium hydroxide aqueous solution was added dropwise to the obtained slurry polymer solution to adjust the pH to 8.5, and the mixture was stirred and washed. The slurry polymer solution was filtered, and ion-exchanged water at 70°C was added and stirred and washed. The pH of the obtained slurry polymer solution was 6.1. Then, the slurry polymer solution was filtered to obtain resin beads. The obtained resin beads were dried overnight at 70°C in a dryer to obtain methacrylic resin beads. The weight average molecular weight Mw of the obtained methacrylic resin beads was 467,000, and the molecular weight distribution Mw / Mn was 1.9. The amount of docosane in the obtained methacrylic resin beads was measured by GC / MS and found to be 80 mass ppm.
[0086] <Examples 2 to 4, 5, 8, 9, and 11, and Comparative Examples 1 and 2> Polymerization was carried out in the same manner as in Example 1 except that the charged composition was as shown in Table 1, to obtain methacrylic resin beads. The temperature trend of Comparative Example 1 is shown in FIG.
[0087] <Comparative Example 3> Polymerization was carried out in the same manner as in Example 2 except that the amount of EHTG was 40 g, to obtain methacrylic resin beads.
[0088] <Comparative Example 4> Polymerization was carried out in the same manner as in Example 4 except that the amount of EHTG was 51 g, to obtain methacrylic resin beads.
[0089] <Example 6> Polymerization was carried out in the same manner as in Example 2 except that the amount of EHTG was 8 g, to obtain methacrylic resin beads.
[0090] <Example 7> Polymerization was carried out in the same manner as in Example 1, except that the amount of EHTG was 4 g and the monomer composition was as shown in Table 1, to obtain methacrylic resin beads.
[0091] <Examples 10, 12, and 13> Polymerization was carried out in the same manner as in Example 2, except that di-(4-tert-butylcyclohexyl) peroxydicarbonate (Perkadox 16), bis(hexadecyloxycarbonyl) peroxide (Trigonox 24-FL), or 1,1'-[dioxybis(carbonyloxy)]ditetradecane (Perkadox 26) was used instead of dilauroyl peroxide (LPO) as the polymerization initiator, and the polymerization temperature was set to 55°C, to obtain methacrylic resin beads.
[0092] <Example 14> Polymerization was carried out in the same manner as in Example 1, except that EHTG was not used and the monomer composition was as shown in Table 1, to obtain methacrylic resin beads.
[0093] <Comparative Example 5> The monomer composition was as shown in Table 1, and polymerization was carried out in the same manner as in Example 1 except that 2000 ppm of docosane was additionally added, to obtain methacrylic resin beads.
[0094] (Active oxygen content) The amount of active oxygen during polymerization was calculated using the following formula. (% by mass of polymerization initiator relative to 100% by mass of the total mass of the monomers of the methacrylic resin used in the thickener) x (amount of active oxygen in the polymerization initiator)
[0095] (Quantitative analysis of docosane, 4-tert-butylcyclohexanol, 1-hexadecanol, 1-tetradecanol and heptane) Approximately 2 g of methacrylic resin beads were weighed as a sample, and dissolved in 40 mL of acetone. 80 mL of methanol was added to the sample, and additives were extracted from the sample by the reprecipitation extraction method. The reprecipitated soluble matter was dried and the volume was adjusted to 10 mL. This solution was subjected to GC measurement under the following measurement conditions. 10.10 mg of docosane standard was precisely weighed out and the volume was adjusted to 10 mL of chloroform to obtain a mixed solution. This was serially diluted, 1 μL of the standard solution was measured, and quantified using the absolute calibration curve method to obtain the mass ratio (ppm by mass) relative to the methacrylic resin beads. The quantitative value was the average value of three repeated measurements. Similarly, 4-tert-butylcyclohexanol, 1-hexadecanol, 1-tetradecanol and heptane were quantified by substituting these substances for docosane in the above quantification method.
[0096] [II. Physical properties of methacrylic resin] (II-1)(Weight average molecular weight (Mw), molecular weight distribution (Mw / Mn)) Except for Example 14, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin beads obtained in the examples and comparative examples were measured using the following apparatus and under the following conditions. Measurement device: gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation. Column: one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series in this order. In this column, high molecular weight compounds elute early, while low molecular weight compounds elute late. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with different molecular weights and known monodisperse peak top molecular weights were used. Peak top molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin. The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin were determined based on the area in the GPC elution curve and the calibration curve of a third-order approximation equation.
[0097] As for Example 14, since the molecular weight was high and outside the molecular weight range of the above-mentioned standard sample for GPC, the absolute molecular weight was measured by GPC-MALS. -GPC-MALS measurement conditions- GPC equipment: Tosoh HLC-8320GPC Column: TSKgel Guard column H XL -H(6.0mmI.D.×4cm)×1 piece +TSKgel GMH XL (7.8mm I.D. x 30cm) x 2 (Tosoh) Detector: RI (differential refractometer) detector MALS :DAWN HELEOS II (manufactured by Wyatt Technology) MALS laser wavelength: 659 nm Eluent: Tetrahydrofuran Flow rate: 1.0 mL / min Column temperature: 40℃ RI detection temperature: 40℃ MALS temperature: room temperature Sample concentration: 0.5mg / ml Sample injection volume: 100 μL
[0098] (II-2) (Volume average particle size) The volume average particle size (μm) of the methacrylic resin beads was measured using the laser scattering method of a Beckman Coulter LS13320.
[0099] (II-3)(Intrinsic viscosity) The intrinsic viscosity of the methacrylic resin beads was measured according to the following procedures 1 to 5. 1. Measurement conditions (1) Equipment used: thermostatic bath, Ubbelohde viscometer (SU), aspirator, stopwatch, chiller, 50 ml measuring flask, syringe (capacity 24 ml), filter (pore size: 0.45 μm, diameter: 25 mm, PTFE) (2) Viscosity measurement conditions: Constant temperature bath: Hot water 25.0℃±1℃ Ubbelohde Viscometer: Viscometer Number OC (3) Solvent used: Chloroform (special grade) (4) Pre-drying conditions for PMMA sample: Dry in a vacuum dryer at 85°C for at least 1 hour. The sample amount for one drying run should be approximately 50 g.
[0100] 2. Sample Solution Preparation (1) Weigh out the sample accurately to the nearest 0.0001 g into a 50 ml measuring flask, within the range of 0.26 g ±0.01. (2) Add approximately 30 ml of chloroform to the measuring flask and dissolve at room temperature by shaking on a shaker. (3) Once the sample has dissolved, add chloroform until the volumetric flask is about 1 cm below the marked line, then immerse it in a thermostatic bath set to a measurement temperature of 25°C and wait for at least 15 minutes. (4) Fill the measuring flask up to the mark with chloroform that has been heated to 25°C in the same thermostatic bath. (5) Keep the sample solution at 25°C in a thermostatic chamber until immediately before measurement. (6) Filter the sample solution using a syringe filter.
[0101] 3. Blank solution measurement The flow time is measured using an Ubbelohde viscometer.
[0102] 4. Sample solution measurement The flow time is measured using an Ubbelohde viscometer.
[0103] 5. Calculation of intrinsic viscosity Calculate the intrinsic viscosity from the measurement results obtained in 3 and 4 using the following formula.
number
[0104] III. Evaluation of thickeners The methacrylic resin beads obtained in the Examples and Comparative Examples were used as a thickener to carry out the following evaluations.
[0105] (III-1) Polymerization behavior The polymerization behavior was evaluated as follows. Polymerization peak temperature is less than 83℃: A (very good, very stable) Polymerization peak temperature is 83℃ or higher but less than 85℃: B (good, stable) Polymerization peak temperature is 85℃ or higher but less than 87℃: C (violent reaction) Polymerization peak temperature is 87℃ or higher: D (violent reaction, unstable)
[0106] (III-2) [Stalling of the Tromsdorff effect] The stall of the Tromsdorff effect was assessed as follows: In the above polymerization, a heat generation peak due to the Trommsdorff effect was observed (a sudden increase in the temperature in the system occurred in the latter stage of the polymerization, and the temperature in the system rose by 1°C or more (for example, the temperature in the system rose by 1°C or more per 5 minutes): A (good) No heat generation peak due to the Tromsdorff effect was observed: B (poor)
[0107] (III-3) Solidification of MMA during melting The obtained beads were dissolved in MMA. The concentration was 15% by mass relative to the total mass of the solution. The dissolution was carried out by weighing the beads in a 2 L beaker so that the total mass was 1000 g, stirring, and heating to a temperature of 70° C. Solidification during dissolution of the MMA was evaluated as follows. After stirring for 2 hours, the viscosity was adjusted without any problems: A Something that has solidified :D
[0108] (III-4) Viscosity upon addition The solutions obtained in (III-3) were evaluated as follows. Those that solidified were marked with "-". A material with a viscosity of 500 mPa·s or more when dissolved at 15% by mass: A When dissolved at 15% by mass, the viscosity is 100 or more and less than 500 mPa·s: B When dissolved at 15% by mass, the viscosity is 50 or more and less than 100 mPa·s: C The viscosity of the material when dissolved at 15% by mass is less than 50 mPa·s: D
[0109] (III-5) Haze during cast polymerization An appropriate amount of the solution obtained in (III-3) was placed in a test tube, and 0.1% by mass of LPO was further added, followed by cast polymerization at 70° C. The haze during cast polymerization was evaluated as follows. A transparent cast polymer was obtained: A Some cloudiness in the center: B Overall cloudiness: C (III-3) Already solidified when melted: D In addition, if haze is observed during cast polymerization, haze and unevenness will occur even when molded into a cast film.
[0110] (III-6) Smell 400g of methacrylic resin beads were placed in a plastic container (sealable, 500mL Eyeboy wide-mouth bottle) and heated at 60℃ for 2 hours. After cooling to 30℃, five evaluators smelled the odor and scored it according to the following criteria. The odor intensity was then ranked from A to D based on the average score of the five evaluators. 6: Unbearable odor 5: Very unpleasant smell 4: An unpleasant smell 3: A strong but not unpleasant smell 2: Slight odor but not unpleasant 1: Hard to feel. The odor intensity was ranked as follows: A (very weak odor): Average score of 5 people is 2 or less B (weak smell): The average score of 5 people is more than 2 and less than 3 C (Good): The average score of 5 people is more than 3 and less than 4. D (Poor): The average score of 5 people is more than 4.
[0111] [Table 1]
[0112] Comparing the Examples and Comparative Examples, it is found that a thickener containing a specific amount of at least one of docosane, 4-tert-butylcyclohexanol, 1-hexadecanol, and 1-tetradecanol can prevent the stall of polymerization due to the failure to exhibit the Trommsdorff effect, and can also prevent solidification when MMA is dissolved. Moreover, it is understood that when the amount of docosane contained in the thickener is too large as in Comparative Example 5, the polymerization becomes unstable, and the haze increases during cast polymerization.
[0113] Furthermore, when comparing graph FIG. 1 showing the temperature trend in the polymerization reaction of Example 1 with graph FIG. 2 showing the temperature trend in the polymerization reaction of Comparative Example 1, it can be seen that while a rapid increase in temperature inside the polymerization tank occurs around 200 minutes in FIG. 1, no such rapid increase in temperature inside the polymerization tank is observed in FIG. 2. [Industrial Applicability]
[0114] According to the present invention, it is possible to provide a thickener that can prevent polymerization stall and deterioration of color due to the failure to manifest the Trommsdorff effect during polymerization, and can prevent solidification due to the progression of the polymerization reaction of methyl methacrylate during dissolution when used in cast polymerization.
Claims
1. 90% by mass or more of a methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000, and A thickening agent containing 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms.
2. The thickener according to claim 1, wherein the methacrylic resin contains 95% by weight or more of methyl methacrylate monomer units and optionally contains 0 to 5% by weight of acrylic ester monomer units.
3. The thickener according to claim 2, wherein the methacrylic resin contains 95 to 99.9% by mass of methyl methacrylate monomer units and 0.1 to 5% by mass of acrylic ester monomer units.
4. The thickener according to claim 2 or 3, wherein the acrylic acid ester monomer unit has an alkyl group having 4 or more carbon atoms.
5. The intrinsic viscosity of the methacrylic resin is 100 to 1000 cm 3 The thickener of claim 1, wherein the viscosity is 1 / g.
6. 2. The thickener according to claim 1, wherein the methacrylic resin is polymerized using a polymerization initiator having a 10-hour half-life temperature of less than 65°C.
7. The thickener according to claim 1, characterized in that the amount of active oxygen when the methacrylic resin is polymerized is 0.001 to 0.01% by mass.
8. The thickener according to claim 1, which is for use in cast polymerization.
9. The thickener according to claim 1, which is used for cast polymerization of a methacrylic resin sheet.
10. The thickener according to claim 1, which is used for cast polymerization of artificial marble.
11. The thickener according to claim 1, which has a volume average particle size of 50 to 500 μm when used in the form of beads.
12. The method for producing a thickener according to claim 1, wherein the methacrylic resin is polymerized using a polymerization initiator having a 10-hour half-life temperature of less than 65°C.
13. 90% by mass or more of a methacrylic resin having a weight average molecular weight of 300,000 to 5,000,000, and A cast film containing 50 to 2000 ppm by mass of one or more compounds selected from the group consisting of docosane, 4-tert-butylcyclohexanol, and aliphatic alcohols having 12 or more carbon atoms.
Citation Information
Patent Citations
Production of methacrylic resin
JP1996109212A
Resin composition, thickener
JP2018178076A
Thickener for cyanoacrylate adhesive
WO2022070868A1